SPIRITUAL ENERGY OF THE UKRAINIAN LITERARY RECONQUISTA AND DYNAMICS OF STYLE PARADIGMS - Maftyn, N. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
Taking into consideration the concepts of the Ukrainian literary thought classics that one way or another touch the problem of the individual author’s style being determined by the idea and aesthetic dominants of the time when the artist creates, the author of the article grounds the notion of “the Ukrainian literary Reconquista style”. The article deals with the spiritual energy of this phenomenon as an effective means of creating a powerful field of national identity as well as the influence of its passionate trend on the dynamics of style paradigms.